2018
DOI: 10.21608/agro.2018.5737.1124
|View full text |Cite
|
Sign up to set email alerts
|

Response of Some Maize Hybrids (Zea mays L.) To NPK Fertilization

Abstract: M ODES MAIzE hybrids need to high amounts of nitrogen, phosphorus and potassium; therefore, two field experiments were conducted at the Experimental Farm of Sids Agricultural Research Station, ARC, Beni-Suef Governorate, Egypt during the two successive seasons of 2015 and 2016 to evaluate the effect of three NPK levels, i.e., 80/6/10, 120/12/20 and 140/18/30kg N, P 2 O 5 and K 2 O/fad , respectively under four maize hybrids, namely, white single cross 10, white three way cross 128, yellow single cross 168 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
2
2
0
Order By: Relevance
“…Mamudu et al (2017) found that increasing N-fertilization rates significantly increased grain yield/feddan. These results are in agreement with Sharifi and Taghizadeh (2009), Badawi et al (2012), Kandil (2013), Modhej et al (2014), Yasin (2016), andAwadalla et al (2018). The recorded data in Table (7) indicate that the interaction between hybrid type and bio-inoculation (H × Bio) was significant on grain yield/feddan, in two seasons.…”
Section: Grain Yield (Ton/feddan)supporting
confidence: 88%
“…Mamudu et al (2017) found that increasing N-fertilization rates significantly increased grain yield/feddan. These results are in agreement with Sharifi and Taghizadeh (2009), Badawi et al (2012), Kandil (2013), Modhej et al (2014), Yasin (2016), andAwadalla et al (2018). The recorded data in Table (7) indicate that the interaction between hybrid type and bio-inoculation (H × Bio) was significant on grain yield/feddan, in two seasons.…”
Section: Grain Yield (Ton/feddan)supporting
confidence: 88%
“…In non-hybrid maize, the maximum mean value of 1000 grain weight (361.43g) was observed with 50% increase over recommended NPK fertilizer (F2), followed by 337.86g with recommended NPK fertilizer (F1), while in hybrid maize, the maximum mean value of 1000 grain weight (380.12g) was observed with F2 followed by (363.8g) with F1 care. These findings corroborate those of Awdalla et al, (2018), who conducted a field experiment over two consecutive seasons in 2015 and 2016 to assess the effect of three NPK levels, namely 80/6/10, 120/12/20, and 140/18/30kg N, P2O5, and K2O/fad, on four maize hybrids, namely white single cross 10, white three way cross 128, yellow single cross 168, and yellow three way 168. The maximum NPK dose resulted in the best growth characteristics, yield and yield elements, and NPK uptake.…”
Section: Csupporting
confidence: 86%
“…), in the 1 st season, and number of rows/ear, ear length and diameter, number of grains/row, ear weight grain protein (%) and protein yield (kg/fed. ), in th 2 nd one as shown in In this connection, a significant differences in yield and its components of maize cultivars were noticed by many authors (Hassan, 1998and 1999, Soliman et al 2004, Shahrokhi and Khorasani, 2013and Awdalla et al 2018. Hassan (1998) who reported that grain yield and its attributes of S.C.103 and T.W.C.310 were superior than that of other maize cultivars.…”
Section: Maize Cultivares Differencesmentioning
confidence: 73%